Conservation in a wicked complex world: challenges and solutions - Game, E.T.; Meijaard, E.; Sheil, D.; McDonald-Madden, E. (Wiley, 2014)
Most conservation challenges are complex and possess all the characteristics of so called “wicked” problems. Despite widespread recognition of this complexity conservationists possess a legacy of institutional structures, tools and practices better suited to simpler systems. We highlight two specific challenges posed by this mismatch: the difficulty of adaptive management where success is ambiguous and the tension between “best practice” and creativity. Drawing on research in other disciplines (including psychology, information systems, business management, and military strategy) we suggest practices that conservation could consider to better respond to complexity. These practices include, defining clear objectives, the use of scenarios, emphasis on pattern analysis, and ensuring greater scope for creative and decentralized decision making. To help illustrate these challenges and solutions, we point to parallels between conservation and military operations.